Simplified Analysis of CD-ROM as an Emergency Solar Panel Alternative - Setiawan, Anggoro Nur; Saefullah, Lalu (JPSE (Journal of Physical Science and Engineering), 2023)
This research aims to analyze the capabilities of CD-ROM discs as solar panels, taking into consideration energy conversion efficiency and temperature effects. The research results indicate that the conversion efficiency of CD-ROM discs is relatively low, averaging around 1.9%, which is still far below conventional solar panels. This efficiency tends to be higher under high sunlight intensity and decreases at higher temperatures. The production cost of CD-ROM discs as solar panels is relatively low compared to conventional solar panels. The environmental impact of using CD-ROM discs as solar panels is also discussed. However, the use of used CD-ROM discs has the potential to reduce electronic waste. Research recommendations include efforts to improve the efficiency of CD-ROM discs, the development of cooling technologies, and a comprehensive evaluation of the environmental impacts throughout the life cycle of CD-ROM discs as solar panels. This research provides a deeper understanding of the potential use of CD-ROM discs as an alternative solar panel and the challenges that need to be addressed for its effective implementation.